Urinary extracellular vesicle N-glycomics identifies diagnostic glycosignatures for bladder cancer - Li, Yang; Fu, Bin; Wang, Maoyu; Chen, Weiyu; Fan, Jiawei; Li, Yueyue; Liu, Xuejiao; Wang, Jun; Zhang, Zhensheng; Lu, Haojie; Zhang, Ying (Nature communications, 2025)
Bladder cancer (BC) is the most common urologic malignancy, facing enormous diagnostic challenges. Urinary extracellular vesicles (EVs) are promising source for developing diagnostic markers for bladder cancer because of the direct contact between urine and bladder. This study pioneers urinary EV N-glycomics for bladder cancer diagnosis. We have generated a comprehensive N-glycome landscape of urinary EVs through high-throughput N-glycome analysis, identifying a total of 252 N-glycans from 333 individuals. In bladder cancer patients, urinary EVs exhibit decreased fucosylation and increased sialylation level. An Eight N-glycan diagnostic model demonstrates strong performance in both validation cohorts, achieving ROC AUC values of 0.88 and 0.86, respectively. Furthermore, this model successfully differentiates both non-muscle invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC) from healthy individuals, underscoring the model’s superiority. Moreover, urinary EVs N-glycoproteomic analysis reveals that the glycoproteins carrying cancer-associated N-glycan signatures are closely associated with immune activities. The N-glycome comparative analysis of EVs and their source cells indicate that the glycosylation profiles of EVs do not completely match the glycosylation backgrounds of their source cells. In summary, our study establishes urinary EV N-glycomics as a non-invasive BC screening tool and provide a framework for EV glycan biomarker discovery across cancers. Bladder cancer diagnosis lacks non-invasive biomarkers. Here, the authors discover urinary extracellular vesicle (EV) glycan signatures that distinguish bladder cancer patients from healthy controls, paving the way for EV-based liquid biopsy.